REVITALISASI PENDIDIKAN AKHLAK MENGHADAPI TANTANGAN DIGITAL DAN HEDONISME REMAJA SMAIT DARUL ILMI - Sabanul Yamin; Nurkholis; Hamdal; Akhmad Khoiri; Kholid Musadad; Fauzan Azzihadin (LPPM STAI Muhammadiyah Probolinggo, 2026)
This community service activity aims to enhance students’ understanding of the importance of moral education in addressing the challenges of the digital era and the growing influence of hedonistic culture among adolescents. The background of this activity is rooted in the increasingly complex moral issues faced by the younger generation due to rapid advancements in information technology and social media, which significantly affect their mindset and behavior. Therefore, revitalizing moral education is essential to instill Islamic values in students’ daily lives. The implementation method consisted of several stages, including preparation and coordination with the school, an opening session with Quran recitation, material presentation by a resource person, and discussion and evaluation sessions. The activity was conducted at SMA IT Darul Ilmi with students as the primary participants. The results indicated that students showed strong enthusiasm and active participation throughout the program. Through interactive sessions, students developed a better understanding of maintaining moral conduct, using digital technology wisely, and filtering negative cultural influences. This activity is expected to contribute positively to strengthening moral education and fostering students’ character based on Islamic values.